AN INVESTIGATION OF SOME HORMONAL BASES FOR ABSCISSION IN COWPEA (VIGNA UNGUICULATA L. WALP.) (1977)
The Investigations carried out on the abscission problem in cowpea are reviewed. The Isolation 5 characterization 9 physiological roles, chemistry, biosynthesis and metabolism of the various groups of plant hormones are also reviewed. Using biological assays and combined gas-liquid chromatography- mass spectrometry (GC-MS, some of the hormones in the extensively purified acidic ethyl acetate extracts obtained from 2-day old and 6-day old cowpea fruits were examined. Biological assays indicated the presence of only Inhibitors in the 2-day old fruits but inhibitors as well as gibberellins and auxins were indicated to be present in the 6-day old fruits, GC-MS analysis of the extract from 2-day old fruits afforded the identification of the known inhibitors, abscisic acid and phaseic acid. 6’-hydroxymethyl abscisic acid was also identified in the extract and this is the first reported evidence that 6’-hydroxymethyl abscisic acid occurs naturally. Several plant hormones were identified (GC-MS analysis) in the extract from 6-day old fruits. These were abscisic acid, phaseic acid, dihydrophaseic acid,’1iso1dihydrophaseic acid, 6’-hydroxyinethy abscisic acid; gibberellins A4, A6, A8, ‘iso’ A8,and A20. Gibberellins A1,A5,and A29 were also believed to be probably present. Two components, believed to be two new gibberellins were also identified in the extract and were tentatively called gibberellins X and Y. Tentative structures were assigned to these two new gibberellins. Purified acidic ethyl acetate extract obtained from fruits that were over six days old was also analysed on the GC-MS. The result was essentially similar to that obtained for the extract from the 6-day old fruits. The crude acidic ethyl acetate extracts from 6-day old seeds and the fruit walls of the 6-day old fruits were also examined on the GC-MS. Several gibberellins were tentatively identified in the extract from the seeds but only one gibberellin could be identified in the extract from the fruit walls. The methyl esters of 16α-hydroxy, 17-hydroxy, and 16α, 17-dihydroxy derivatives of gibberellin A34 and the 16-epimers of the last two compounds were synthesized from gibberellin A4. This was done in order to correlate the structures that were tentatively assigned to the two new gibberellins with the natural compounds. The disparity in the hormonal contents of the 6-day old and 2-day old fruits is discussed in relation to the abscission problem in cowpea.